Chronic hand eczema in Germany: 5-year follow-up data from the CARPE registry - Apfelbacher, Christian; Ofenloch, Robert; Weisshaar, Elke; Diepgen, Thomas L. (Contact dermatitis, 2019)
Background The CARPE registry was set up in 2009 to prospectively investigate the management of patients with chronic hand eczema (CHE). Objectives To report comprehensive follow-up data from the CARPE registry. Patients and methods We investigated sociodemographic and clinical characteristics, provision of medical care, physician-assessed outcomes, and patient-reported outcomes (PROs). Data were collected between 2009 and 2016, with up to 5 years of follow-up, and are reported descriptively. Results Overall, 1281 patients were included in the registry (53.7% female). Mean age was 47.0 years. Of the patients, 793 and 231 completed the 2-year follow-up and 5-year follow-up, respectively. At baseline, 5.4% had changed or given up their job because of CHE, the average duration of CHE was 6.1 years, and, in 22.4%, the CHE was severe according to physician global assessment. Systemic treatment (alitretinoin, acitretin, and methotrexate) was prescribed at least once to 39.0% of the patients during the course of the follow-up. Disease severity, quality of life and treatment satisfaction improved over time, and the proportion of patients receiving systemic treatments decreased. Conclusions Under continued dermatological care, substantial improvements in disease severity and PROs over time was achieved during the course of the CARPE registry, even in patients with long-standing and severe hand eczema.